Why so different? A case study about Floras from a Mediterranean island - Bagella, Simonetta; Becca, Giovanna; Bedini, Gianni; Caria, Maria Carmela; Pisanu, Stefania; Urbani, Malvina; Usai, Maria Franca; Filigheddu, Rossella (Phytotaxa, 2020)
In light of the hypothesis that different authors, who have access to the same information and tools, can give different interpretations of the same reality, namely the vascular plants, existing within a determinate geographic boundary, this research aims to verify how and to what extent these differences can affect a checklist, and what critical issues and positive effects may arise in them. To this purpose, we compared two different checklists which were developed approximately in the same period for the same geographic area, the island of Sardinia (Italy). The results show that checklists of the same area can differ in quantitative terms, establishing a different value of floristic richness. Moreover, they can differ in qualitative terms due to the different approach adopted by the authors concerning nomenclature, taxonomy, and interpretation, delimitation, and circumscription of taxa. These discrepancies may have positive side effects as they offer insights for critical reviews and further investigation.